ASEAN economic community scorecard : performance and perception - Das, Sanchita Basu. (Singapore : Institute of Southeast Asian Studies, 2013)
During the 13th ASEAN Summit in November 2007, ASEAN Leaders endorsed the ASEAN Economic Community (AEC) Blueprint, which laid the foundation of creating a'single market and production base' among the ten Southeast Asian economies. Soon after that, ASEAN faced great uncertainties in the light of the 2008 global financial crisis and continues to remain cautious in the face of the ongoing global economic weakness. Despite this, the region is forging ahead with its commitment to carry out economic liberalization and cooperation as stipulated in the AEC Blueprint.
Includes bibliographica references and index.
Keywords: Southeast Asia -- Economic integration; Southeast Asia -- Economic conditions; Southeast Asia -- Foreign economic relations